ENVIRONMENTS OF IMMEDIATE STRATEGIES, LACK OF CONFIDENCE, AND THE RELATIONSHIP WITH DARK TRIAD PERSONALITY TRAITS - Jefferson, Jadir (Health and Society, 2023)
This narrative review deals with the correlation between personal, professional, and institutional lack of confidence, based on the Inter-American Development Bank (IDB) study. This correlation is associated with hostile environments that require immediate strategies, studied in the life course theory. The main replicating agents of these effects are based on social relationships involving individuals or groups exhibiting narcissistic, Machiavellian, and psychopathic personality traits, described in numerous scientific articles as Dark Triad personality traits. Such a condition indicates the uncertainty that the laws and justice will be fulfilled equally for all if there is any attempt of deceit or non-compliance with regulations. Under these circumstances, development is compromised, opportunities become scarce, education, health, housing, security, and the entire personal and professional environment becomes unstable, insecure, and unfair. The permanent effects of a continuum of immediate responses result in the absence of punishment and lessening actions of reprimand for justice, turning this environment fertile for individuals with dishonest, selfish, manipulative, and low empathy personalities, forming a cycle of permanent cause and effect.